A clinicopathological reappraisal of intraductal papillary neoplasm of the bile duct (IPNB): a continuous spectrum with papillary cholangiocarcinoma in 181 curatively resected cases. Issue 10 (October 2021) - Onoe, Shunsuke; Ebata, Tomoki; Yokoyama, Yukihiro; Igami, Tsuyoshi; Mizuno, Takashi; Yamaguchi, Junpei; Watanabe, Nobuyuki; Otsuka, Shinpei; Nakamura, Shigeo; Shimoyama, Yoshie; Nagino, Masato
Abstract: Background: Intraductal papillary neoplasm of the bile-duct (IPNB) has recently been further subclassified into "so-called IPNBs" (Type-1) and "narrow-sense papillary cholangiocarcinomas" (Type-2), but their differential diagnosis is challenging. This study aimed to reevaluate Type-1 and Type-2 IPNBs. Methods: Consecutive patients who underwent papillary bile-duct tumor resection were included. Using six pathological features (location, mucin secretion, histological architecture, histological type, presence of a low/intermediate-dysplasia component, and proportion of the invasive component), all papillary tumors were scored. Tumors scoring 5–6 were classified as Type-1, 0–1 as Type-2, and 2–4 as Type-Unclassifiable. Results: The 181 papillary bile-duct tumor patients were divided into three groups, consisting of 12 Type-1, 46 Type-2, and 123 Type-Unclassifiable—gray-zone lesions between Type-1 and Type-2 that constituted the largest proportion of papillary tumors. Type-1 tumors were pathologically the least advanced, while the other types showed gradual advancement. The 5-year survival rate was better for patients with Type-1 tumors than for those with Type-Unclassifiable or Type-2 tumors. Conclusion: The scoring system worked well to delineate a continuous spectrum of pathologic features ranging from Type-1, through Type-Unclassifiable, to Type-2, the latter two being challenging to differentially diagnose. Type-1 is regarded as an early neoplasm of Type-Unclassifiable and Type-2.